EFFEC OF DECALICIFICATION ON BORON ADSORPTION IN SOME CALCAREOUS SOIL IN NORTHERN OF IRAQ. - M. A. J Al-Obaidi (Mesopotamia Journal of Agriculture)
Boron adsorption have been studied in eight decalcified surface soil in Ninevah province using a quiet equilibrium with different boron concentration as a boric acid levels (0 , 2.5 , 7.5 , 10) mg Boron L –1 . Adsorption was described by two Langmuir equation of a single and double surface & Frendlich equation before and after decalcification. It was appeared that the maximum adsorption was textured found in the fine soil. Before decalcification the results showed that boron maximum adsorption was significantly correlated with both total and active lime, Organic matter and clay contents. The bonding energy in calcareous soil before decalcification was dereased from (0.5 – 0.9) to (0.3 – 0.6) ml. gm –1 after decalcification, and the bonding engergy was increased in the soft textured soil that gives evident for the high boron boning and its difficult phase to the liquid phase, adsorption capacity reduced from (42 - 72) before decalcification to (36 – 60) gm –1. Both surface Langmuir equation referred to two kinds of soil surfaces. The first one was characterized by low adsorption capacity and high bonding energy while, the seemed was characterized by high adsorption capacity and low bonding energy for the second surface.